2019
DOI: 10.1590/0370-44672017720018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfate on the pitting potential of austenitic stainless steels 18Cr8Ni and 17Cr6Mn5Ni in chloride media

Abstract: Pitting corrosion resistance of two austenitic stainless steels, 18Cr8Ni (Type 304L or UNS S30403 stainless steel) and 17Cr6Mn5Ni, was evaluated in three electrolytic solutions containing a fixed concentration of 0.6M sodium chloride and different additions of sodium sulfate, 0.06M, 0.15M or 0.6M. Cyclic potentiodynamic polarization tests were performed on as-received samples and on specimens annealed at 1010°C, 1040°C, 1070°C or 1100°C. The best pitting corrosion resistance was presented by the 17Cr6Mn5Ni ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the electrolyte with the sulfate concentration. It can be found that the addition of sodium sulfate inhibits pitting corrosion and has a better inhibitor effect in SS (Calderón-Hernández, Hincapíe-Ladino, Magnabosco, & Alonso-Falleiros, 2019;Vazquez-Arenas & Pritzker, 2010). In the steels used in the present investigation, there is not expected a considerable occurrence of MnS due to low S content.…”
Section: Electrochemical Characterization During Rubbing and Irradiationmentioning
confidence: 58%
See 1 more Smart Citation
“…In the electrolyte with the sulfate concentration. It can be found that the addition of sodium sulfate inhibits pitting corrosion and has a better inhibitor effect in SS (Calderón-Hernández, Hincapíe-Ladino, Magnabosco, & Alonso-Falleiros, 2019;Vazquez-Arenas & Pritzker, 2010). In the steels used in the present investigation, there is not expected a considerable occurrence of MnS due to low S content.…”
Section: Electrochemical Characterization During Rubbing and Irradiationmentioning
confidence: 58%
“…The charge transfer resistance (reaction resistance) of the corrosion reaction increased as a result of increasing the diameter of the semicircle which increases with increasing the exposure time. The impedance plots that have not appeared as a semicircle at different times for the samples that have not been exposed to irradiation may be assigned for the frequency dispersion in addition to the inhomogeneity of the surface (Calderón-Hernández et al, 2019).…”
Section: Electrochemical Characterization During Rubbing and Irradiationmentioning
confidence: 99%
“…According to the authors [43,44], the passivation effect of sulfate ions plays an important role in the formation of a highly resistant passive film. The authors [45] explain the increase in The use of (NH 4 ) 2 SO 4 solution as an electrolyte for the plasma polishing process may have contributed to the high corrosion resistance of both PEP and PPEP surfaces. According to the authors [43,44], the passivation effect of sulfate ions plays an important role in the formation of a highly resistant passive film.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%
“…According to the authors [43,44], the passivation effect of sulfate ions plays an important role in the formation of a highly resistant passive film. The authors [45] explain the increase in resistance of the austenitic stainless steel to the pitting by an adsorption of sulfate anions on the passive film surface.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%